Perioperative complications in cleft palate repair with Robin sequence following Tuebingen palatal plate treatment. Issue 4 (April 2021) - Naros, Andreas; Krimmel, Michael; Zengerle, Franziska; Bacher, Margit; Koos, Bernd; Mack, Ulrich; Wiechers, Cornelia; Poets, Christian F.; Reinert, Siegmar
Abstract: Our study aimed to evaluate perioperative complications following our institutional pre- and intraoperative management in cleft palate repair with Robin sequence (RS). RS patients who underwent cleft palate repair between 2000 and 2020 were retrospectively analysed. RS children with complete documentation and whose initial treatment involved the Tuebingen palatal plate (TPP) were included. Clinical records and operative charts were reviewed with regard to clinical characteristics as well as the neonatal and perioperative course. Results before and after adjustment of the anesthesiology protocol in 2014 were compared. 143 RS patients (41% male, 59% female) were included. Median pretherapeutic mixed-obstructive apnea index (MOAI) after birth was 9.4/hour (IQR 20.0). TPP treatment was associated with normalisation of the MOAI and adequate weight gain until surgery. At surgery, median age was 10 months (IQR 3), MOAI 0.1/h (IQR 0.5), and weight 8.7 kg (IQR 1.7). In 93% of cases ( n = 133), the postoperative course was uneventful. Refinement of the anesthesiology protocol showed positive effects on the perioperative course and led to a reduction in perioperative events (10.7% vs. 2.9%). No severe perioperative complications occurred. We recommend the adoption of TPP treatment in the therapy of RS children. Our favourable results show that early TPP treatment minimizes perioperative complications in cleft palate repair by effectively and sustainably correcting upper airway obstruction.